Upaya Preventif Diabetes Mellitus Sejak Dini Melalui Edukasi di SMA YMI Wonopringgo Pekalongan - Rofiqoh, Siti; Widyastuti, Windha; Isyti'aroh, Isyti'aroh; Pratiwi, Yuni Sandra; Wirotomo, Tri Sakti (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pekajangan Pekalongan, 2025)
Abstract Various risk factors for DM have been identified. Efforts to prevent DM can be done by controlling risk factors early on through healthy living efforts. The lack of knowledge causes teenagers to be unable to adopt healthy lifestyles as an effort to prevent DM. The aim of this activity is to increase the knowledge of the scout supervising teacher and the YMI Wonopringgo Pekalongan High School scout student group about DM disease and its prevention, so that they are able to disseminate knowledge to other students. The activity took the form of providing information to them. Counseling is given once. The results of the activity showed that the average initial knowledge score was 53 and the final score was 63. The conclusion was the increase average knowledge score of the scout student group at YMI Wonopringgo Pekalongan High School after delivered health education about DM. It is recommended that community health center officers continuously provide health education to the public about non-communicable diseases including DM. Keywords: Diabetes mellitus; early; education; preventive.